2020
DOI: 10.3389/fpsyt.2020.00458
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Screen Time, Fast Foods, Sugar-Sweetened Beverages and Depressive Symptoms in Chinese Adolescents

Abstract: Objective: Although previous studies have shown that screen time (ST), fast foods (FFs) and sugar-sweetened beverages (SSBs) consumption are associated with depressive symptoms in adolescents, research on these associations in Chinese adolescents is scarce. This study aimed to examine the association between ST, FFs, SSBs and depressive symptoms in Chinese adolescents, and explore the mediating effects of FFs and SSBs in the association between ST and depressive symptoms.Methods: This school-based nationwide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…Other studies found similar results when analyzing these factors separately [49][50][51]. SSBs consumption is accompanied by several health risks, in which alcohol consumption and smoking are considered as not only as gateways for the use of other substances [19], but also risk factors for the development of mental disorders [19][20][21][22]. Thus, measures that reduce SSBs consumption as well as the use of alcohol and tobacco, are essential in ensuring adolescents' physical and psychological health.…”
Section: Plos Onementioning
confidence: 60%
See 1 more Smart Citation
“…Other studies found similar results when analyzing these factors separately [49][50][51]. SSBs consumption is accompanied by several health risks, in which alcohol consumption and smoking are considered as not only as gateways for the use of other substances [19], but also risk factors for the development of mental disorders [19][20][21][22]. Thus, measures that reduce SSBs consumption as well as the use of alcohol and tobacco, are essential in ensuring adolescents' physical and psychological health.…”
Section: Plos Onementioning
confidence: 60%
“…According to the World Health Organization (WHO), SSBs consumption is a harmful food habit and is considered to be a risk factor for chronic non-communicable diseases (NCD) due to the resulting increase in the intake of free sugars [10]. Excessive consumption of these beverages by adolescents is associated with overweight and obesity [11][12][13][14][15], NCD [16][17][18], and mental disorders [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It was possible to evaluate the association between the characteristics of the school food environment and SSB consumption in this cross-sectional study of Brazilian adolescents. It is important to emphasize that the consumption of these beverages with high energy density and low nutritional value causes damage to adolescent health (5,6,8,9,(11)(12)(13)(14), and a reduction in their consumption has been hence recommended (20).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the Food and Nutritional Surveillance System identified that in 2019, 65% of adolescents (n = 235,590) consumed SSB the day before the interview (2). Excessive consumption of SSB by adolescents has been associated with them being overweight and obese (3)(4)(5)(6)(7), the incidence of chronic non-communicable diseases (8)(9)(10), and the incidence of mental disorders (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that depression in adolescents may be associated with risky behaviors such as insufficient levels of physical activity [ 11 , 12 , 13 , 14 ], psychoactive substance use [ 15 ], unhealthy eating habits [ 16 , 17 , 18 ], and risky sexual behavior [ 19 , 20 ]. Experts argue that there may be a positive relationship between physical activity and brain health in adolescents, which involves both cognitive function and mental health [ 14 ].…”
Section: Introductionmentioning
confidence: 99%